The Evolution and Transformation of Bankside, London, 1947-2019. (January 2021) - Murray, Stephen
The redevelopment of the Bankside area in central London was proposed in 1943, yet substantive regeneration was only achieved toward the end of the century. This article analyzes the processes whereby a postwar industrial, then deindustrial, locality evolved into a popular leisure and residential quarter. It argues that strategic plans for the area engendered only incremental and piecemeal redevelopment. Change was principally driven by industrial decline, government building policies, and the availability of finance, and, since the 1990s, by private-sector investment and culture-driven regeneration. Tensions and conflicts arose over the direction of, sometimes controversial, redevelopment. The locality's principal building, Bankside power station, inhibited the realization of early redevelopment plans, but, as Tate Modern, was instrumental in the cultural and social transformation of the area.